Hollow warm-keeping fiber and preparation method thereof
Through the combination of modified hollow composite microspheres and modified polypropylene, hollow warm fibers are prepared by coaxial electrospinning technology, which solves the problem that polypropylene fibers are susceptible to ultraviolet rays, oxygen and heat, and achieves good warmth and resistance Electrostatic and mechanical properties, and improve anti-aging ability.
Patent Information
- Application Number
- CN202411639877.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-18
- Publication Date
- 2024-12-17
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Polypropylene fibers are susceptible to ultraviolet rays, oxygen and heat to cause performance degradation, limiting their development prospects in certain applications.
After reacting ethyl orthosilicate with cationic polystyrene microspheres, it is reacted with tetrabutyl titanate and pyrrole mixture to prepare modified hollow composite microspheres, and protect 10-undecol and The amino-protected 3-amino-3-(3,5-di-tert-butyl-4-hydroxyphenyl)-propionic acid reaction forms modified polypropylene fibers, and hollow warm fibers are produced by coaxial electrospinning.
Hollow warm fibers have good warm, anti-static, mechanical and anti-aging properties, extending their performance life.
Smart Images

Figure SMS_2 
Figure SMS_3 
Figure SMS_4
Abstract
Description
Technical Field
[0001] The invention relates to the field of fibers, in particular to a hollow thermal insulation fiber and a preparation method thereof. Background Art
[0002] Cold is one of the natural challenges that threaten human survival, and clothing is one of the effective ways for humans to resist severe cold. With the improvement of living standards and the change of human ideology, people began to pursue lightweight and warm clothing. Polypropylene fiber with low density advantage has become one of the ideal materials for preparing lightweight and warm insulation fabrics.
[0003] Polypropylene fiber is a synthetic fiber made of polypropylene resin. It has many advantages, such as light weight, high strength, chemical corrosion resistance, good insulation and low price. However, polypropylene fiber also has some disadvantages, such as being susceptible to ultraviolet rays, oxygen and heat and aging, resulting in performance degradation, which limits its development prospects in certain application ranges. The hollow thermal insulation fabric prepared by the present invention not only has good thermal insulation performance, but also has good antistatic performance, mechanical properties and anti-aging performance, and has broad market prospects. Summary of the invention
[0004] The purpose of the present invention is to provide a hollow thermal insulation fiber and a preparation method thereof to solve the problems existing in the prior art.
[0005] In order to solve the above technical problems, the present invention provides the following technical solutions: A hollow thermal insulation fiber, wherein the hollow thermal insulation fiber is prepared by reacting tetraethyl orthosilicate with cationic polystyrene microspheres, then reacting with tetrabutyl titanate, calcining, and reacting with a pyrrole mixed solution to obtain a modified hollow composite microsphere; reacting triisobutylaluminum-protected 10-undecenol with propylene, then reacting with amino-protected 3-amino-3-(3,5-di-tert-butyl-4-hydroxyphenyl)-propionic acid, immersing in glacial acetic acid, and drying to obtain a modified polypropylene; and preparing a shell spinning solution from the modified hollow composite microspheres and the modified polypropylene through coaxial electrospinning.
[0006] A method for preparing a hollow thermal insulation fiber comprises the following steps: (1) Cationic polystyrene microspheres, ammonia water and anhydrous ethanol are mixed in a mass ratio of 1: (2-4): (10-20), and tetraethyl orthosilicate, triethanolamine and anhydrous ethanol are mixed in a mass ratio of 1: (0.6-0.8): (13-17) and added dropwise at a rate of 1-3 ml / L. After the addition is completed, the mixture is stirred at 200-400 r / min at 35-45 °C for 4-6 h, cooled to room temperature, and centrifuged to separate the precipitate. The precipitate is washed with deionized water for 3-5 times, and vacuum dried at 55-65 °C for 4-6 h to obtain cationic polystyrene silica microspheres; cationic polystyrene silica microspheres, Deionized water and anhydrous ethanol are mixed in a mass ratio of 1: (3-5): (8-12) and ultrasonicated for 20-40 minutes, tetrabutyl titanate (3-5 times the mass of cationic polystyrene silica microspheres) is added dropwise at a rate of 1-3 ml / L, and the pH is adjusted to 4.8-5.2 with acetic acid. After the addition is completed, the mixture is stirred at 200-400 r / min at 75-85°C for 4-6 hours, and the precipitate is separated by centrifugation. The precipitate is washed with deionized water for 3-5 times, vacuum dried at 55-65°C for 4-6 hours, and calcined at 450-550°C in a muffle furnace for 3-5 hours to obtain hollow composite microspheres of titanium dioxide and silicon dioxide. (2) The hollow composite microspheres and deionized water were mixed at a mass ratio of 1:(14-16), stirred at 300-500 r / min at 0-4°C, and the pyrrole mixture of 3-7 times the mass of the hollow composite microspheres was uniformly added dropwise within 10-15 min. After the addition was completed, stirring was continued for 25-35 min. A 1% ferric chloride aqueous solution of 14-16 times the mass of the hollow composite microspheres was added dropwise at a rate of 1-1.2 mL / min. After the addition was completed, stirring was continued for 10-12 h. The precipitate was separated by centrifugation, and the precipitate was washed with deionized water and anhydrous ethanol for 3-5 times, respectively, and vacuum dried at 40-50°C for 6-8 h to obtain the modified hollow composite microspheres. (3) Triisobutylaluminum-protected 10-undecanol, 2,6-di-tert-butyl-4-methylphenol, methylaluminoxane, dimethylsilylbis(2-methyl-4-phenylindenyl)zirconium dichloride, and toluene are mixed in a mass ratio of 1: (0.03-0.05): (0.2-0.4): (0.1-0.3): (13-17) and added into a reactor. The reaction temperature is 40-50°C, the propylene pressure is 4 bar, and the reaction time is 15 minutes to obtain a primary product. The primary product is immersed in a hydrochloric acid / ethanol solution for 10-20 minutes, filtered, dissolved in toluene at 90-100°C, and purified to obtain hydroxylated polypropylene; (4) Mix hydroxylated polypropylene, amino-protected 3-amino-3-(3,5-di-tert-butyl-4-hydroxyphenyl)-propionic acid, 90% sulfuric acid solution, and toluene in a mass ratio of 1: (0.6-0.8): (0.2-0.4): (8-12), and stir at 95-105°C and 400-600 r / min for 3-5 hours under a nitrogen atmosphere to obtain a polypropylene composite material; immerse the polypropylene composite material in glacial acetic acid, and stir at room temperature at 300-500 r / min for 2-4 hours to obtain a modified polypropylene; (5) Mix modified polypropylene, modified hollow composite microspheres, dichloromethane, and N,N-dimethylacetamide in a mass ratio of 1: (0.2-0.4): (7-9): (0.8-1.2), and stir at 400-600 r / min for 10-14 h at 15-25 °C to obtain a shell spinning solution; mix polyvinyl alcohol, dichloromethane, and dimethyl sulfoxide in a mass ratio of 1: (5-15): (15-25), and stir at 400-600 r / min for 3-5 h at 20-30 °C to obtain a core spinning solution; load the shell spinning solution and the core spinning solution into syringes respectively, and perform coaxial electrospinning in an electrospinning machine to obtain primary fibers; (6) The nascent fibers were immersed in deionized water, ultrasonically treated at 40-50 °C for 2-4 h, allowed to stand at room temperature for 40-44 h, with the water replaced every 2 h, and vacuum dried at 60-70 °C for 3-5 h to obtain hollow thermal insulation fibers.
[0007] As an optimization, the cationic polystyrene microspheres in step (1) are nano-scale cationic polystyrene microspheres purchased from Xi'an Ruixi Biotechnology Co., Ltd.
[0008] As an optimization, the pyrrole mixed solution in step (2) is prepared by mixing pyrrole, pyrrole-3-carboxaldehyde and anhydrous ethanol in a mass ratio of 1: (0.3-0.4): (12-14).
[0009] As an optimization, the triisobutylaluminum-protected 10-undecenol in step (3) is prepared by dropping triisobutylaluminum into 10-undecenol with a molar number of 0.7 to 0.9 times that of triisobutylaluminum at 0° C. under a nitrogen atmosphere, and stirring at 400 to 600 r / min for 3 to 5 hours.
[0010] As an optimization, the reaction process for preparing hydroxylated polypropylene in step (3) is as follows: .
[0011] As an optimization, the preparation method of the hydrochloric acid / ethanol solution in step (3) is: mixing hydrochloric acid and anhydrous ethanol in a mass ratio of 1:5.
[0012] As an optimization, the preparation method of the amino-protected 3-amino-3-(3,5-di-tert-butyl-4-hydroxyphenyl)-propionic acid in step (4) is: 3-amino-3-(3,5-di-tert-butyl-4-hydroxyphenyl)-propionic acid, di-tert-butyl dicarbonate, 1 mol / L sodium hydroxide solution, and tert-butanol are mixed in a mass ratio of 1: (1.3-1.7): (2-4): (8-12), stirred at room temperature at 300-500 r / min for 2-4 h, and obtained by recrystallization.
[0013] As an optimization, the coaxial electrospinning process parameters of step (5) are: shell layer propulsion rate 0.9 ml / h, core layer propulsion rate 0.3 ml / h, voltage 23 kV, receiving distance 12 cm, and ambient humidity 40-50%.
[0014] Compared with the prior art, the beneficial effects achieved by the present invention are: When preparing the hollow thermal insulation fiber, the present invention comprises the following steps: reacting tetraethyl orthosilicate with cationic polystyrene microspheres, and then reacting with tetrabutyl titanate, and then reacting with a pyrrole mixed solution after calcination to obtain a modified hollow composite microsphere; reacting triisobutylaluminum-protected 10-undecenol with propylene, and then reacting with amino-protected 3-amino-3-(3,5-di-tert-butyl-4-hydroxyphenyl)-propionic acid, and then immersing in glacial acetic acid and drying to obtain a modified polypropylene; and preparing the shell spinning solution from the modified hollow composite microspheres and the modified polypropylene through coaxial electrostatic spinning to obtain the fiber.
[0015] Firstly, hollow composite microspheres of silica and titanium dioxide are prepared using cationic polystyrene microspheres as templates. After calcination, the template agent is removed to form a hollow structure with silica as an inner shell layer and titanium dioxide as an outer shell layer. The inner silica shell layer has a low thermal conductivity, and the outer titanium dioxide shell layer can reflect and refract ultraviolet rays, so that the hollow thermal insulation fiber has good thermal insulation performance and ultraviolet resistance. The hollow composite microspheres react with a pyrrole mixture, and pyrrole and pyrrole derivatives are oxidatively polymerized on the surface of the hollow composite microspheres under the action of an oxidant to form polypyrrole. Polypyrrole, as a conjugated conductive polymer, has conductive properties and high conductivity, and can improve the antistatic properties of the hollow thermal insulation fiber. Pyrrole-3-carboxaldehyde in the pyrrole mixture introduces aldehyde groups into the modified hollow composite microspheres, and reacts with the amino groups on the modified polypropylene to form a stable cross-linked structure, thereby improving the mechanical properties of the hollow thermal insulation fiber.
[0016] Secondly, 3-amino-3-(3,5-di-tert-butyl-4-hydroxyphenyl)-propionic acid has two relatively active reaction sites, namely, carboxyl and amino. The amino group on 3-amino-3-(3,5-di-tert-butyl-4-hydroxyphenyl)-propionic acid is reacted with di-tert-butyl dicarbonate to protect the amino group. After the amino group on 3-amino-3-(3,5-di-tert-butyl-4-hydroxyphenyl)-propionic acid is protected, the carboxyl group and the hydroxyl group on the hydroxylated polypropylene form a stable cross-linking structure through an esterification reaction, thereby improving the mechanical properties of the hollow thermal insulation fiber. 3-amino-3-(3,5-di-tert-butyl-4-hydroxyphenyl)-propionic acid itself, as a macromolecular hindered phenol, has a good anti-aging effect in polypropylene fibers. DETAILED DESCRIPTION
[0017] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention. Example 1
[0018] A method for preparing a hollow thermal insulation fiber comprises the following steps: (1) Cationic polystyrene microspheres, ammonia water and anhydrous ethanol were mixed in a mass ratio of 1:2:10, and tetraethyl orthosilicate, triethanolamine and anhydrous ethanol were mixed in a mass ratio of 1:0.6:13 and added dropwise at a rate of 1 ml / L. After the addition was completed, the mixture was stirred at 200 r / min at 35 °C for 4 h, cooled to room temperature, and centrifuged to separate the precipitate. The precipitate was washed with deionized water for 3 times, and vacuum dried at 55 °C for 4 h to obtain cationic polystyrene silica microspheres; cationic polystyrene silica microspheres were prepared. The microspheres, deionized water and anhydrous ethanol were mixed in a mass ratio of 1:3:8 and ultrasonicated for 20 minutes. Tetrabutyl titanate, which was 3 times the mass of cationic polystyrene silica microspheres, was added dropwise at a rate of 1 ml / L. The pH was adjusted to 4.8 with acetic acid. After the addition was completed, the mixture was stirred at 200 r / min at 75 ° C for 4 hours. The precipitate was separated by centrifugation. The precipitate was washed 3 times with deionized water, vacuum dried at 55 ° C for 4 hours, and calcined at 450 ° C for 3 hours in a muffle furnace to obtain hollow composite microspheres of titanium dioxide and silicon dioxide. (2) Pyrrole, pyrrole-3-carboxaldehyde and anhydrous ethanol were mixed in a mass ratio of 1:0.3:12 to obtain a pyrrole mixed solution; hollow composite microspheres and deionized water were mixed in a mass ratio of 1:14, stirred at 300 r / min at 0°C, and the pyrrole mixed solution 3 times the mass of the hollow composite microspheres was uniformly added dropwise within 10 minutes. After the addition was completed, stirring was continued for 25 minutes; a 1% ferric chloride aqueous solution 14 times the mass of the hollow composite microspheres was added dropwise at a rate of 1 mL / min. After the addition was completed, stirring was continued for 10 hours. The precipitate was separated by centrifugation, and the precipitate was washed 3 times with deionized water and anhydrous ethanol respectively, and vacuum dried at 40°C for 6 hours to obtain modified hollow composite microspheres; (3) Triisobutylaluminum was dripped into 10-undecenol with a molar number of 0.7 times that of triisobutylaluminum at 0°C under nitrogen atmosphere, and stirred at 400-600 r / min for 3 h to obtain triisobutylaluminum-protected 10-undecenol; triisobutylaluminum-protected 10-undecenol, 2,6-di-tert-butyl-4-methylphenol, methylaluminoxane, dimethylsilylbis(2-methyl-4-phenylindenyl)zirconium dichloride, and toluene were mixed in a mass ratio of 1:0.03:0.2:0.1:13 and added into a reactor, and the reaction temperature was 40°C, the propylene pressure was 4 bar, and the reaction time was 15 minutes to obtain a primary product; hydrochloric acid and anhydrous ethanol were mixed in a mass ratio of 1:5 to obtain a hydrochloric acid / ethanol solution; the primary product was immersed in the hydrochloric acid / ethanol solution for 10 min, filtered, dissolved in toluene at 90°C, and purified to obtain hydroxylated polypropylene; (4) 3-amino-3-(3,5-di-tert-butyl-4-hydroxyphenyl)-propionic acid, di-tert-butyl dicarbonate, 1 mol / L sodium hydroxide solution, and tert-butanol were mixed in a mass ratio of 1:1.3:2:8, stirred at room temperature at 300 r / min for 2 h, and recrystallized to obtain amino-protected 3-amino-3-(3,5-di-tert-butyl-4-hydroxyphenyl)-propionic acid; hydroxylated polypropylene, amino-protected 3-amino-3-(3,5-di-tert-butyl-4-hydroxyphenyl)-propionic acid, 90% sulfuric acid solution, and toluene were mixed in a mass ratio of 1:0.6:0.2:8, stirred at 95°C and 400 r / min for 3 h under a nitrogen atmosphere to obtain a polypropylene composite material; the polypropylene composite material was immersed in glacial acetic acid, stirred at room temperature at 300 r / min for 2 h to obtain a modified polypropylene; (5) Modified polypropylene, modified hollow composite microspheres, dichloromethane, and N,N-dimethylacetamide were mixed in a mass ratio of 1:0.2:7:0.8, and stirred at 400 r / min for 10 h at 15°C to obtain a shell spinning solution; polyvinyl alcohol, dichloromethane, and dimethyl sulfoxide were mixed in a mass ratio of 1:5:15, and stirred at 400 r / min for 3 h at 20°C to obtain a core spinning solution; the shell spinning solution and the core spinning solution were respectively loaded into syringes, and coaxial electrospinning was performed in an electrospinning machine. The electrospinning process parameters were: shell propulsion rate 0.9 ml / h, core propulsion rate 0.3 ml / h, voltage 23 kV, receiving distance 12 cm, and ambient humidity 40%, to obtain primary fibers; (6) The nascent fibers were immersed in deionized water, ultrasonically treated at 40 °C for 2 h, allowed to stand at room temperature for 40 h, with the water replaced every 2 h, and vacuum dried at 60 °C for 3 h to obtain hollow thermal insulation fibers. Example 2
[0019] A method for preparing a hollow thermal insulation fiber comprises the following steps: (1) Cationic polystyrene microspheres, ammonia water and anhydrous ethanol were mixed in a mass ratio of 1:3:15, and tetraethyl orthosilicate, triethanolamine and anhydrous ethanol were mixed in a mass ratio of 1:0.7:15 and then added dropwise at a rate of 2 ml / L. After the addition was completed, the mixture was stirred at 300 r / min at 40°C for 5 h, cooled to room temperature, centrifuged and precipitated, washed with deionized water for 4 times, and vacuum dried at 60°C for 5 h to obtain cationic polystyrene silica microspheres; cationic polystyrene silica The microspheres, deionized water and anhydrous ethanol were mixed in a mass ratio of 1:4:10 and ultrasonicated for 30 minutes. Tetrabutyl titanate, which was 4 times the mass of cationic polystyrene silica microspheres, was added dropwise at a rate of 2 ml / L. The pH was adjusted to 5 with acetic acid. After the addition was completed, the mixture was stirred at 300 r / min at 80°C for 5 hours. The precipitate was separated by centrifugation. The precipitate was washed 4 times with deionized water, vacuum dried at 60°C for 5 hours, and calcined at 500°C in a muffle furnace for 4 hours to obtain hollow composite microspheres of titanium dioxide and silicon dioxide. (2) Pyrrole, pyrrole-3-carboxaldehyde and anhydrous ethanol were mixed in a mass ratio of 1:0.35:13 to obtain a pyrrole mixed solution; hollow composite microspheres and deionized water were mixed in a mass ratio of 1:15, stirred at 400 r / min at 2°C, and the pyrrole mixed solution of 5 times the mass of the hollow composite microspheres was added dropwise at a uniform rate within 12.5 min. After the addition was completed, stirring was continued for 30 min; a 1% ferric chloride aqueous solution of 15 times the mass of the hollow composite microspheres was added dropwise at a rate of 1.1 mL / min. After the addition was completed, stirring was continued for 11 h. The precipitate was separated by centrifugation, and the precipitate was washed 4 times with deionized water and anhydrous ethanol respectively, and vacuum dried at 45°C for 7 h to obtain modified hollow composite microspheres; (3) Triisobutylaluminum was dripped into 10-undecenol with a molar number of 0.8 times that of triisobutylaluminum at 0°C under nitrogen atmosphere, and stirred at 500 r / min for 4 h to obtain triisobutylaluminum-protected 10-undecenol; triisobutylaluminum-protected 10-undecenol, 2,6-di-tert-butyl-4-methylphenol, methylaluminoxane, dimethylsilylbis(2-methyl-4-phenylindenyl)zirconium dichloride, and toluene were mixed in a mass ratio of 1:0.04:0.3:0.2:15 and added into a reactor. The reaction temperature was 45°C, the propylene pressure was 4 bar, and the reaction time was 15 min to obtain a primary product; hydrochloric acid and anhydrous ethanol were mixed in a mass ratio of 1:5 to obtain a hydrochloric acid / ethanol solution; the primary product was immersed in the hydrochloric acid / ethanol solution for 15 min, filtered, dissolved in toluene at 95°C, and purified to obtain hydroxylated polypropylene; (4) 3-amino-3-(3,5-di-tert-butyl-4-hydroxyphenyl)-propionic acid, di-tert-butyl dicarbonate, 1 mol / L sodium hydroxide solution, and tert-butanol were mixed in a mass ratio of 1:1.5:3:10, stirred at room temperature at 400 r / min for 3 h, and recrystallized to obtain amino-protected 3-amino-3-(3,5-di-tert-butyl-4-hydroxyphenyl)-propionic acid; hydroxylated polypropylene, amino-protected 3-amino-3-(3,5-di-tert-butyl-4-hydroxyphenyl)-propionic acid, 90% sulfuric acid solution, and toluene were mixed in a mass ratio of 1:0.7:0.3:10, stirred at 100°C and 500 r / min for 4 h under a nitrogen atmosphere to obtain a polypropylene composite material; the polypropylene composite material was immersed in glacial acetic acid, stirred at room temperature at 400 r / min for 3 h to obtain a modified polypropylene; (5) Modified polypropylene, modified hollow composite microspheres, dichloromethane, and N,N-dimethylacetamide were mixed in a mass ratio of 1:0.3:8:1, and stirred at 500 r / min for 12 h at 20 °C to obtain a shell spinning solution; polyvinyl alcohol, dichloromethane, and dimethyl sulfoxide were mixed in a mass ratio of 1:10:20, and stirred at 500 r / min for 4 h at 25 °C to obtain a core spinning solution; the shell spinning solution and the core spinning solution were respectively loaded into syringes, and coaxial electrospinning was performed in an electrospinning machine. The electrospinning process parameters were: shell layer propulsion rate 0.9 ml / h, core layer propulsion rate 0.3 ml / h, voltage 23 kV, receiving distance 12 cm, and ambient humidity 45%, to obtain primary fibers; (5) The nascent fibers were immersed in deionized water, ultrasonically treated at 45 °C for 3 h, allowed to stand at room temperature for 42 h, with the water replaced every 2 h, and vacuum dried at 65 °C for 4 h to obtain hollow thermal insulation fibers. Example 3
[0020] A method for preparing a hollow thermal insulation fiber comprises the following steps: (1) Cationic polystyrene microspheres, ammonia water and anhydrous ethanol were mixed in a mass ratio of 1:4:20, and tetraethyl orthosilicate, triethanolamine and anhydrous ethanol were mixed in a mass ratio of 1:0.8:17 and then added dropwise at a rate of 3 ml / L. After the addition was completed, the mixture was stirred at 400 r / min at 45°C for 6 h, cooled to room temperature, and centrifuged to separate the precipitate. The precipitate was washed with deionized water for 5 times, and vacuum dried at 65°C for 6 h to obtain cationic polystyrene silica microspheres; cationic polystyrene silica microspheres were prepared. The microspheres, deionized water and anhydrous ethanol were mixed in a mass ratio of 1:5:12 and ultrasonicated for 40 minutes, tetrabutyl titanate with a mass of 5 times that of cationic polystyrene silica microspheres was added dropwise at a rate of 3 ml / L, and the pH was adjusted to 5.2 with acetic acid. After the addition was completed, the mixture was stirred at 400 r / min at 85°C for 6 hours, and the precipitate was separated by centrifugation. The precipitate was washed with deionized water for 5 times, vacuum dried at 65°C for 6 hours, and calcined at 550°C in a muffle furnace for 5 hours to obtain hollow composite microspheres of titanium dioxide and silicon dioxide. (2) Pyrrole, pyrrole-3-carboxaldehyde and anhydrous ethanol were mixed in a mass ratio of 1:0.4:14 to obtain a pyrrole mixed solution; hollow composite microspheres and deionized water were mixed in a mass ratio of 1:16, stirred at 500 r / min at 4°C, and the pyrrole mixed solution of 7 times the mass of the hollow composite microspheres was uniformly added dropwise within 15 minutes. After the addition was completed, stirring was continued for 35 minutes; a 1% ferric chloride aqueous solution of 16 times the mass of the hollow composite microspheres was added dropwise at a rate of 1.2 mL / min. After the addition was completed, stirring was continued for 12 hours. The precipitate was separated by centrifugation, and the precipitate was washed 5 times with deionized water and anhydrous ethanol respectively, and vacuum dried at 50°C for 8 hours to obtain modified hollow composite microspheres; (3) Triisobutylaluminum was dripped into 10-undecenol with a molar number of 0.9 times that of triisobutylaluminum at 0°C under nitrogen atmosphere, and stirred at 600 r / min for 5 h to obtain triisobutylaluminum-protected 10-undecenol; triisobutylaluminum-protected 10-undecenol, 2,6-di-tert-butyl-4-methylphenol, methylaluminoxane, dimethylsilylbis(2-methyl-4-phenylindenyl)zirconium dichloride, and toluene were mixed in a mass ratio of 1:0.05:0.4:0.3:17 and added into a reactor. The reaction temperature was 50°C, the propylene pressure was 4 bar, and the reaction time was 15 minutes to obtain a primary product; hydrochloric acid and anhydrous ethanol were mixed in a mass ratio of 1:5 to obtain a hydrochloric acid / ethanol solution; the primary product was immersed in the hydrochloric acid / ethanol solution for 10-20 min, filtered, dissolved in toluene at 100°C, and purified to obtain hydroxylated polypropylene; (4) 3-amino-3-(3,5-di-tert-butyl-4-hydroxyphenyl)-propionic acid, di-tert-butyl dicarbonate, 1 mol / L sodium hydroxide solution, and tert-butanol were mixed in a mass ratio of 1:1.7:4:12, stirred at room temperature at 500 r / min for 4 h, and recrystallized to obtain amino-protected 3-amino-3-(3,5-di-tert-butyl-4-hydroxyphenyl)-propionic acid; hydroxylated polypropylene, amino-protected 3-amino-3-(3,5-di-tert-butyl-4-hydroxyphenyl)-propionic acid, 90% sulfuric acid solution, and toluene were mixed in a mass ratio of 1:0.8:0.4:12, stirred at 105°C and 600 r / min for 5 h under a nitrogen atmosphere to obtain a polypropylene composite material; the polypropylene composite material was immersed in glacial acetic acid, stirred at room temperature at 500 r / min for 4 h to obtain a modified polypropylene; (5) Modified polypropylene, modified hollow composite microspheres, dichloromethane, and N,N-dimethylacetamide were mixed in a mass ratio of 1:0.4:9:1.2, and stirred at 600 r / min for 14 h at 25 °C to obtain a shell spinning solution; polyvinyl alcohol, dichloromethane, and dimethyl sulfoxide were mixed in a mass ratio of 1:15:25, and stirred at 600 r / min for 5 h at 30 °C to obtain a core spinning solution; the shell spinning solution and the core spinning solution were respectively loaded into syringes, and coaxial electrospinning was performed in an electrospinning machine. The electrospinning process parameters were: shell layer propulsion rate 0.9 ml / h, core layer propulsion rate 0.3 ml / h, voltage 23 kV, receiving distance 12 cm, and ambient humidity 50%, to obtain primary fibers; (6) The nascent fibers were immersed in deionized water, ultrasonically treated at 50 °C for 4 h, allowed to stand at room temperature for 44 h, with the water replaced every 2 h, and vacuum dried at 70 °C for 5 h to obtain hollow thermal insulation fibers.
[0021] Comparative Example 1 A method for preparing a hollow thermal insulation fiber comprises the following steps: (1) Cationic polystyrene microspheres, ammonia water and anhydrous ethanol were mixed in a mass ratio of 1:3:15, and tetraethyl orthosilicate, triethanolamine and anhydrous ethanol were mixed in a mass ratio of 1:0.7:15 and then added dropwise at a rate of 2 ml / L. After the addition was completed, the mixture was stirred at 300 r / min at 40°C for 5 h, cooled to room temperature, centrifuged and precipitated, washed with deionized water for 4 times, and vacuum dried at 60°C for 5 h to obtain cationic polystyrene silica microspheres; cationic polystyrene silica The microspheres, deionized water and anhydrous ethanol were mixed in a mass ratio of 1:4:10 and ultrasonicated for 30 minutes. Tetrabutyl titanate, which was 4 times the mass of cationic polystyrene silica microspheres, was added dropwise at a rate of 2 ml / L. The pH was adjusted to 5 with acetic acid. After the addition was completed, the mixture was stirred at 300 r / min at 80°C for 5 hours. The precipitate was separated by centrifugation. The precipitate was washed 4 times with deionized water, vacuum dried at 60°C for 5 hours, and calcined at 500°C in a muffle furnace for 4 hours to obtain hollow composite microspheres of titanium dioxide and silicon dioxide. (2) Pyrrole and anhydrous ethanol were mixed in a mass ratio of 1:13 to prepare a pyrrole solution; hollow composite microspheres and deionized water were mixed in a mass ratio of 1:15, stirred at 400 r / min at 2°C, and 5 times the mass of the hollow composite microspheres of the pyrrole solution were uniformly added dropwise within 12.5 min, and the stirring was continued for 30 min after the addition was completed; 15 times the mass of the hollow composite microspheres and a 1% ferric chloride aqueous solution were added dropwise at a rate of 1.1 mL / min, and the stirring was continued for 11 h after the addition was completed, and the precipitate was separated by centrifugation, and the precipitate was washed 4 times with deionized water and anhydrous ethanol respectively, and vacuum dried at 45°C for 7 h to obtain modified hollow composite microspheres; (3) Triisobutylaluminum was dripped into 10-undecenol with a molar number of 0.8 times that of triisobutylaluminum at 0°C under nitrogen atmosphere, and stirred at 500 r / min for 4 h to obtain triisobutylaluminum-protected 10-undecenol; triisobutylaluminum-protected 10-undecenol, 2,6-di-tert-butyl-4-methylphenol, methylaluminoxane, dimethylsilylbis(2-methyl-4-phenylindenyl)zirconium dichloride, and toluene were mixed in a mass ratio of 1:0.04:0.3:0.2:15 and added into a reactor. The reaction temperature was 45°C, the propylene pressure was 4 bar, and the reaction time was 15 min to obtain a primary product; hydrochloric acid and anhydrous ethanol were mixed in a mass ratio of 1:5 to obtain a hydrochloric acid / ethanol solution; the primary product was immersed in the hydrochloric acid / ethanol solution for 15 min, filtered, dissolved in toluene at 95°C, and purified to obtain hydroxylated polypropylene; (4) 3-amino-3-(3,5-di-tert-butyl-4-hydroxyphenyl)-propionic acid, di-tert-butyl dicarbonate, 1 mol / L sodium hydroxide solution, and tert-butanol were mixed in a mass ratio of 1:1.5:3:10, stirred at room temperature at 400 r / min for 3 h, and recrystallized to obtain amino-protected 3-amino-3-(3,5-di-tert-butyl-4-hydroxyphenyl)-propionic acid; hydroxylated polypropylene, amino-protected 3-amino-3-(3,5-di-tert-butyl-4-hydroxyphenyl)-propionic acid, 90% sulfuric acid solution, and toluene were mixed in a mass ratio of 1:0.7:0.3:10, stirred at 100°C and 500 r / min for 4 h under a nitrogen atmosphere to obtain a polypropylene composite material; the polypropylene composite material was immersed in glacial acetic acid, stirred at room temperature at 400 r / min for 3 h to obtain a modified polypropylene; (5) Modified polypropylene, modified hollow composite microspheres, dichloromethane, and N,N-dimethylacetamide were mixed in a mass ratio of 1:0.3:8:1, and stirred at 500 r / min for 12 h at 20 °C to obtain a shell spinning solution; polyvinyl alcohol, dichloromethane, and dimethyl sulfoxide were mixed in a mass ratio of 1:10:20, and stirred at 500 r / min for 4 h at 25 °C to obtain a core spinning solution; the shell spinning solution and the core spinning solution were respectively loaded into syringes, and coaxial electrospinning was performed in an electrospinning machine. The electrospinning process parameters were: shell layer propulsion rate 0.9 ml / h, core layer propulsion rate 0.3 ml / h, voltage 23 kV, receiving distance 12 cm, and ambient humidity 45%, to obtain primary fibers; (6) The nascent fibers were immersed in deionized water, ultrasonicated at 45 °C for 3 h, allowed to stand at room temperature for 42 h, with the water replaced every 2 h, and vacuum dried at 65 °C for 4 h to obtain hollow thermal insulation fibers.
[0022] Comparative Example 2 A method for preparing a hollow thermal insulation fiber comprises the following steps: (1) Cationic polystyrene microspheres, ammonia water and anhydrous ethanol were mixed in a mass ratio of 1:3:15, and tetraethyl orthosilicate, triethanolamine and anhydrous ethanol were mixed in a mass ratio of 1:0.7:15 and then added dropwise at a rate of 2 ml / L. After the addition was completed, the mixture was stirred at 300 r / min at 40°C for 5 h, cooled to room temperature, centrifuged and precipitated, washed with deionized water for 4 times, and vacuum dried at 60°C for 5 h to obtain cationic polystyrene silica microspheres; cationic polystyrene silica The microspheres, deionized water and anhydrous ethanol were mixed in a mass ratio of 1:4:10 and ultrasonicated for 30 minutes. Tetrabutyl titanate, which was 4 times the mass of cationic polystyrene silica microspheres, was added dropwise at a rate of 2 ml / L. The pH was adjusted to 5 with acetic acid. After the addition was completed, the mixture was stirred at 300 r / min at 80°C for 5 hours. The precipitate was separated by centrifugation. The precipitate was washed 4 times with deionized water, vacuum dried at 60°C for 5 hours, and calcined at 500°C in a muffle furnace for 4 hours to obtain hollow composite microspheres of titanium dioxide and silicon dioxide. (2) Triisobutylaluminum was dripped into 10-undecenol with a molar number of 0.8 times that of triisobutylaluminum at 0°C under nitrogen atmosphere, and stirred at 500 r / min for 4 h to obtain triisobutylaluminum-protected 10-undecenol; triisobutylaluminum-protected 10-undecenol, 2,6-di-tert-butyl-4-methylphenol, methylaluminoxane, dimethylsilylbis(2-methyl-4-phenylindenyl)zirconium dichloride, and toluene were mixed in a mass ratio of 1:0.04:0.3:0.2:15 and added into a reactor, the reaction temperature was 45°C, the propylene pressure was 4 bar, and the reaction time was 15 min to obtain a primary product; hydrochloric acid and anhydrous ethanol were mixed in a mass ratio of 1:5 to obtain a hydrochloric acid / ethanol solution; the primary product was immersed in the hydrochloric acid / ethanol solution for 15 min, filtered, dissolved in toluene at 95°C, and purified to obtain hydroxylated polypropylene; (3) 3-amino-3-(3,5-di-tert-butyl-4-hydroxyphenyl)-propionic acid, di-tert-butyl dicarbonate, 1 mol / L sodium hydroxide solution, and tert-butanol were mixed in a mass ratio of 1:1.5:3:10, stirred at room temperature at 400 r / min for 3 h, and recrystallized to obtain amino-protected 3-amino-3-(3,5-di-tert-butyl-4-hydroxyphenyl)-propionic acid; hydroxylated polypropylene, amino-protected 3-amino-3-(3,5-di-tert-butyl-4-hydroxyphenyl)-propionic acid, 90% sulfuric acid solution, and toluene were mixed in a mass ratio of 1:0.7:0.3:10, stirred at 100°C and 500 r / min for 4 h under a nitrogen atmosphere to obtain a polypropylene composite material; the polypropylene composite material was immersed in glacial acetic acid, stirred at room temperature at 400 r / min for 3 h to obtain a modified polypropylene; (4) Modified polypropylene, hollow composite microspheres, dichloromethane, and N,N-dimethylacetamide were mixed in a mass ratio of 1:0.3:8:1, and stirred at 20°C and 500 r / min for 12 h to obtain a shell spinning solution; polyvinyl alcohol, dichloromethane, and dimethyl sulfoxide were mixed in a mass ratio of 1:10:20, and stirred at 25°C and 500 r / min for 4 h to obtain a core spinning solution; the shell spinning solution and the core spinning solution were respectively loaded into syringes, and coaxial electrospinning was performed in an electrospinning machine. The electrospinning process parameters were: shell propulsion rate 0.9 ml / h, core propulsion rate 0.3 ml / h, voltage 23 kV, receiving distance 12 cm, and ambient humidity 45%, to obtain primary fibers; (5) The nascent fibers were immersed in deionized water, ultrasonically treated at 45 °C for 3 h, allowed to stand at room temperature for 42 h, with the water replaced every 2 h, and vacuum dried at 65 °C for 4 h to obtain hollow thermal insulation fibers.
[0023] Comparative Example 3 A method for preparing a hollow thermal insulation fiber comprises the following steps: (1) Pyrrole, pyrrole-3-carboxaldehyde and anhydrous ethanol were mixed in a mass ratio of 1:0.35:13 to prepare a pyrrole mixed solution; a 1% ferric chloride aqueous solution with a mass concentration of 0.05 times the mass of the pyrrole mixed solution was added dropwise at a rate of 1.1 mL / min, and stirring was continued for 11 hours after the addition was completed. The precipitate was separated by centrifugation, and the precipitate was washed with deionized water and anhydrous ethanol for 4 times respectively, and vacuum dried at 45°C for 7 hours to obtain polypyrrole; (2) Triisobutylaluminum was dripped into 10-undecenol with a molar number of 0.8 times that of triisobutylaluminum at 0°C under nitrogen atmosphere, and stirred at 500 r / min for 4 h to obtain triisobutylaluminum-protected 10-undecenol; triisobutylaluminum-protected 10-undecenol, 2,6-di-tert-butyl-4-methylphenol, methylaluminoxane, dimethylsilylbis(2-methyl-4-phenylindenyl)zirconium dichloride, and toluene were mixed in a mass ratio of 1:0.04:0.3:0.2:15 and added into a reactor, the reaction temperature was 45°C, the propylene pressure was 4 bar, and the reaction time was 15 min to obtain a primary product; hydrochloric acid and anhydrous ethanol were mixed in a mass ratio of 1:5 to obtain a hydrochloric acid / ethanol solution; the primary product was immersed in the hydrochloric acid / ethanol solution for 15 min, filtered, dissolved in toluene at 95°C, and purified to obtain hydroxylated polypropylene; (3) 3-amino-3-(3,5-di-tert-butyl-4-hydroxyphenyl)-propionic acid, di-tert-butyl dicarbonate, 1 mol / L sodium hydroxide solution, and tert-butanol were mixed in a mass ratio of 1:1.5:3:10, stirred at room temperature at 400 r / min for 3 h, and recrystallized to obtain amino-protected 3-amino-3-(3,5-di-tert-butyl-4-hydroxyphenyl)-propionic acid; hydroxylated polypropylene, amino-protected 3-amino-3-(3,5-di-tert-butyl-4-hydroxyphenyl)-propionic acid, 90% sulfuric acid solution, and toluene were mixed in a mass ratio of 1:0.7:0.3:10, stirred at 100°C and 500 r / min for 4 h under a nitrogen atmosphere to obtain a polypropylene composite material; the polypropylene composite material was immersed in glacial acetic acid, stirred at room temperature at 400 r / min for 3 h to obtain a modified polypropylene; (4) Modified polypropylene, polypyrrole, dichloromethane, and N,N-dimethylacetamide were mixed in a mass ratio of 1:0.3:8:1, and stirred at 20°C and 500 r / min for 12 h to obtain a shell spinning solution; polyvinyl alcohol, dichloromethane, and dimethyl sulfoxide were mixed in a mass ratio of 1:10:20, and stirred at 25°C and 500 r / min for 4 h to obtain a core spinning solution; the shell spinning solution and the core spinning solution were respectively loaded into syringes, and coaxial electrospinning was performed in an electrospinning machine. The electrospinning process parameters were: shell propulsion rate 0.9 ml / h, core propulsion rate 0.3 ml / h, voltage 23 kV, receiving distance 12 cm, and ambient humidity 45%, to obtain primary fibers; (5) The nascent fibers were immersed in deionized water, ultrasonically treated at 45 °C for 3 h, allowed to stand at room temperature for 42 h, with the water replaced every 2 h, and vacuum dried at 65 °C for 4 h to obtain hollow thermal insulation fibers.
[0024] Comparative Example 4 A method for preparing a hollow thermal insulation fiber comprises the following steps: (1) Cationic polystyrene microspheres, ammonia water and anhydrous ethanol were mixed in a mass ratio of 1:3:15, and tetraethyl orthosilicate, triethanolamine and anhydrous ethanol were mixed in a mass ratio of 1:0.7:15 and then added dropwise at a rate of 2 ml / L. After the addition was completed, the mixture was stirred at 300 r / min at 40°C for 5 h, cooled to room temperature, centrifuged and precipitated, washed with deionized water for 4 times, and vacuum dried at 60°C for 5 h to obtain cationic polystyrene silica microspheres; cationic polystyrene silica The microspheres, deionized water and anhydrous ethanol were mixed in a mass ratio of 1:4:10 and ultrasonicated for 30 minutes. Tetrabutyl titanate, which was 4 times the mass of cationic polystyrene silica microspheres, was added dropwise at a rate of 2 ml / L. The pH was adjusted to 5 with acetic acid. After the addition was completed, the mixture was stirred at 300 r / min at 80°C for 5 hours. The precipitate was separated by centrifugation. The precipitate was washed 4 times with deionized water, vacuum dried at 60°C for 5 hours, and calcined at 500°C in a muffle furnace for 4 hours to obtain hollow composite microspheres of titanium dioxide and silicon dioxide. (2) Pyrrole, pyrrole-3-carboxaldehyde and anhydrous ethanol were mixed in a mass ratio of 1:0.35:13 to obtain a pyrrole mixed solution; hollow composite microspheres and deionized water were mixed in a mass ratio of 1:15, stirred at 400 r / min at 2°C, and the pyrrole mixed solution of 5 times the mass of the hollow composite microspheres was added dropwise at a uniform rate within 12.5 min. After the addition was completed, stirring was continued for 30 min; a 1% ferric chloride aqueous solution of 15 times the mass of the hollow composite microspheres was added dropwise at a rate of 1.1 mL / min. After the addition was completed, stirring was continued for 11 h. The precipitate was separated by centrifugation, and the precipitate was washed 4 times with deionized water and anhydrous ethanol respectively, and vacuum dried at 45°C for 7 h to obtain modified hollow composite microspheres; (3) 10-undecenol, 2,6-di-tert-butyl-4-methylphenol, methylaluminoxane, dimethylsilylbis(2-methyl-4-phenylindenyl)zirconium dichloride and toluene were mixed in a mass ratio of 1:0.04:0.3:0.2:15 and added into a reactor. The reaction temperature was 45°C, the propylene pressure was 4 bar, and the reaction time was 15 minutes to obtain hydroxylated polypropylene. (4) 3-amino-3-(3,5-di-tert-butyl-4-hydroxyphenyl)-propionic acid, di-tert-butyl dicarbonate, 1 mol / L sodium hydroxide solution, and tert-butanol were mixed in a mass ratio of 1:1.5:3:10, stirred at room temperature at 400 r / min for 3 h, and recrystallized to obtain amino-protected 3-amino-3-(3,5-di-tert-butyl-4-hydroxyphenyl)-propionic acid; hydroxylated polypropylene, amino-protected 3-amino-3-(3,5-di-tert-butyl-4-hydroxyphenyl)-propionic acid, 90% sulfuric acid solution, and toluene were mixed in a mass ratio of 1:0.7:0.3:10, stirred at 100°C and 500 r / min for 4 h under a nitrogen atmosphere to obtain a polypropylene composite material; the polypropylene composite material was immersed in glacial acetic acid, stirred at room temperature at 400 r / min for 3 h to obtain a modified polypropylene; (5) Modified polypropylene, modified hollow composite microspheres, dichloromethane, and N,N-dimethylacetamide were mixed in a mass ratio of 1:0.3:8:1, and stirred at 500 r / min for 12 h at 20 °C to obtain a shell spinning solution; polyvinyl alcohol, dichloromethane, and dimethyl sulfoxide were mixed in a mass ratio of 1:10:20, and stirred at 500 r / min for 4 h at 25 °C to obtain a core spinning solution; the shell spinning solution and the core spinning solution were respectively loaded into syringes, and coaxial electrospinning was performed in an electrospinning machine. The electrospinning process parameters were: shell layer propulsion rate 0.9 ml / h, core layer propulsion rate 0.3 ml / h, voltage 23 kV, receiving distance 12 cm, and ambient humidity 45%, to obtain primary fibers; (6) The nascent fibers were immersed in deionized water, ultrasonicated at 45 °C for 3 h, allowed to stand at room temperature for 42 h, with the water replaced every 2 h, and vacuum dried at 65 °C for 4 h to obtain hollow thermal insulation fibers.
[0025] Comparative Example 5 A method for preparing a hollow thermal insulation fiber comprises the following steps: (1) Cationic polystyrene microspheres, ammonia water and anhydrous ethanol were mixed in a mass ratio of 1:3:15, and tetraethyl orthosilicate, triethanolamine and anhydrous ethanol were mixed in a mass ratio of 1:0.7:15 and then added dropwise at a rate of 2 ml / L. After the addition was completed, the mixture was stirred at 300 r / min at 40°C for 5 h, cooled to room temperature, centrifuged and precipitated, washed with deionized water for 4 times, and vacuum dried at 60°C for 5 h to obtain cationic polystyrene silica microspheres; cationic polystyrene silica The microspheres, deionized water and anhydrous ethanol were mixed in a mass ratio of 1:4:10 and ultrasonicated for 30 minutes. Tetrabutyl titanate, which was 4 times the mass of cationic polystyrene silica microspheres, was added dropwise at a rate of 2 ml / L. The pH was adjusted to 5 with acetic acid. After the addition was completed, the mixture was stirred at 300 r / min at 80°C for 5 hours. The precipitate was separated by centrifugation. The precipitate was washed 4 times with deionized water, vacuum dried at 60°C for 5 hours, and calcined at 500°C in a muffle furnace for 4 hours to obtain hollow composite microspheres of titanium dioxide and silicon dioxide. (2) Pyrrole, pyrrole-3-carboxaldehyde and anhydrous ethanol were mixed in a mass ratio of 1:0.35:13 to obtain a pyrrole mixed solution; hollow composite microspheres and deionized water were mixed in a mass ratio of 1:15, stirred at 400 r / min at 2°C, and 0.35 times the mass of the hollow composite microspheres of the pyrrole mixed solution were uniformly added dropwise within 12.5 minutes. After the addition was completed, stirring was continued for 30 minutes; 15 times the mass of the hollow composite microspheres and a 1% ferric chloride aqueous solution were added dropwise at a rate of 1.1 mL / min. After the addition was completed, stirring was continued for 11 hours. The precipitate was separated by centrifugation, and the precipitate was washed 4 times with deionized water and anhydrous ethanol respectively, and vacuum dried at 45°C for 7 hours to obtain modified hollow composite microspheres; (3) Triisobutylaluminum was dripped into 10-undecenol with a molar number of 0.8 times that of triisobutylaluminum at 0°C under nitrogen atmosphere, and stirred at 500 r / min for 4 h to obtain triisobutylaluminum-protected 10-undecenol; triisobutylaluminum-protected 10-undecenol, 2,6-di-tert-butyl-4-methylphenol, methylaluminoxane, dimethylsilylbis(2-methyl-4-phenylindenyl)zirconium dichloride, and toluene were mixed in a mass ratio of 1:0.04:0.3:0.2:15 and added into a reactor. The reaction temperature was 45°C, the propylene pressure was 4 bar, and the reaction time was 15 min to obtain a primary product; hydrochloric acid and anhydrous ethanol were mixed in a mass ratio of 1:5 to obtain a hydrochloric acid / ethanol solution; the primary product was immersed in the hydrochloric acid / ethanol solution for 15 min, filtered, dissolved in toluene at 95°C, and purified to obtain hydroxylated polypropylene; (4) Hydroxylated polypropylene, modified hollow composite microspheres, dichloromethane, and N,N-dimethylacetamide were mixed in a mass ratio of 1:0.3:8:1, and stirred at 500 r / min for 12 h at 20°C to obtain a shell spinning solution; polyvinyl alcohol, dichloromethane, and dimethyl sulfoxide were mixed in a mass ratio of 1:10:20, and stirred at 500 r / min for 4 h at 25°C to obtain a core spinning solution; the shell spinning solution and the core spinning solution were respectively loaded into syringes, and coaxial electrospinning was performed in an electrospinning machine. The electrospinning process parameters were: shell propulsion rate 0.9 ml / h, core propulsion rate 0.3 ml / h, voltage 23 kV, receiving distance 12 cm, and ambient humidity 45%, to obtain primary fibers; (5) The nascent fibers were immersed in deionized water, ultrasonically treated at 45 °C for 3 h, allowed to stand at room temperature for 42 h, with the water replaced every 2 h, and vacuum dried at 65 °C for 4 h to obtain hollow thermal insulation fibers.
[0026] Test Example 1 Thermal insulation performance test: Test method: The hollow thermal insulation fibers prepared in each embodiment and comparative example were knitted into a fabric with a double rib structure using a BCM / 60RG multifunctional double-sided knitting circular machine. The knitting process parameters were: barrel diameter 16 inches, number of passes 8, and rotation speed 15r / min. Referring to GB / T 35762-2017 "Textile Thermal Transfer Performance Test Method Flat Plate Method", a YG606 fabric thermal resistance meter was used. Under the standard test environment of 20°C and 65%RH, the sample preheating time was 40 minutes, the sample test time was 40 minutes, and each fabric was tested twice, and the average value was taken. The results are shown in Table 1.
[0027] Table 1
[0028] From the comparison of the experimental data of Examples 1 to 3 and Comparative Examples 1 to 5 in Table 1, it can be found that the hollow thermal insulation fiber prepared by the present invention has good thermal insulation performance.
[0029] By comparison, the thermal conductivity of Examples 1 to 3 is significantly greater than that of Comparative Example 3, indicating that the hollow composite microspheres of silica and titanium dioxide prepared using cationic polystyrene microspheres as templates form a hollow structure by removing the template agent after calcination, and the silica shell layer has a low thermal conductivity, which makes the hollow thermal insulation fiber have good thermal insulation performance.
[0030] Test Example 2 Antistatic performance test: Test method: The resistivity was tested using the ST2253 digital four-probe tester produced by Suzhou Jingge Electronics Co., Ltd. The fiber was crushed into powder, passed through a 100-mesh sieve, and pressed into a thin sheet under a pressure of 50 kg for testing. The results are shown in Table 2.
[0031] Table 2
[0032] From the comparison of the experimental data of Examples 1 to 3 and Comparative Examples 1 to 5 in Table 2, it can be found that the hollow thermal insulation fiber prepared by the present invention has good antistatic performance.
[0033] By comparison, the resistivity of Examples 1 to 3 is lower than that of Comparative Examples 2 and 3, indicating that the hollow composite microspheres react with the pyrrole mixed solution, and pyrrole and pyrrole derivatives are oxidatively polymerized on the surface of the hollow composite microspheres under the action of the oxidant to form polypyrrole. Polypyrrole, as a conjugated conductive polymer, has conductive properties and high conductivity. Its introduction into polypropylene fibers can improve the antistatic properties of the hollow thermal insulation fibers.
[0034] Test Example 3 Mechanical properties test: Test method: The mechanical properties of the embodiment and the comparative example were tested using the XL-1A filament tensile tester. The sample was passed around the yarn guide hook and the yarn guide wheel, and passed downward through the upper and lower clamps to ensure that the sample was straightened without relaxation. A pre-tension of about 10 cN was applied to the sample. The lower clamp drove the sample downward until the sample broke and then returned to its original position to obtain the breaking strength of the sample. The clamping distance was 250 mm, the tensile speed was 250 mm / min, and each sample was repeated more than 10 times, and the test results were averaged. The results are shown in Table 3.
[0035] Table 3
[0036] From the comparison of the experimental data of Examples 1 to 3 and Comparative Examples 1 to 5 in Table 3, it can be found that the hollow thermal insulation fiber prepared by the present invention has good mechanical properties.
[0037] By comparison, the breaking strength of Examples 1 to 3 is significantly greater than that of Comparative Examples 1, 2, and 5, indicating that pyrrole-3-carboxaldehyde in the pyrrole mixture introduces aldehyde groups into the modified hollow composite microspheres, and the hydroxylated polypropylene and the amino-protected 3-amino-3-(3,5-di-tert-butyl-4-hydroxyphenyl)-propionic acid are cross-linked through an esterification reaction to release the amino group again, and the aldehyde group and the amino group undergo a Schiff base reaction to form a stable cross-linked structure, which effectively improves the mechanical properties of the hollow thermal insulation fiber.
[0038] Test Example 4 Anti-aging performance test: Test method: Aging treatment method: immerse the hollow thermal insulation fiber in 1000 mg / L sodium hypochlorite solution, seal it, place it in a water bath at 60°C for 24 hours, take it out and dry it at 105°C for 4 hours; Fracture strength loss rate test: According to the test method of test example 3, the fracture strength before and after aging treatment was tested, and the fracture strength loss rate was calculated. Each sample was repeated more than 10 times, and the test results were averaged. The results are shown in Table 4.
[0039] Table 4
[0040] From the comparison of the experimental data of Examples 1 to 3 and Comparative Examples 1 to 5 in Table 4, it can be found that the hollow thermal insulation fiber prepared by the present invention has good anti-aging performance.
[0041] By comparison, the breaking strength loss rate of Examples 1 to 3 is significantly greater than that of Comparative Example 5, indicating that the hindered phenol 3-amino-3-(3,5-di-tert-butyl-4-hydroxyphenyl)-propionic acid is introduced in the preparation process of the hollow thermal insulation fiber. The tert-butyl groups on both sides of the hydroxyl group on the benzene ring of 3-amino-3-(3,5-di-tert-butyl-4-hydroxyphenyl)-propionic acid increase its steric hindrance, and the hydrogen atoms on the hydroxyl group are easy to fall off and combine with free radicals to form stable phenoloxy free radicals, thereby terminating the free radical chain reaction, preventing further oxidation, and improving the anti-aging performance of the hollow thermal insulation fiber.
[0042] The specific implementation methods described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific implementation method of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.
Claims
1. A hollow thermal insulation fiber, characterized in that: The hollow thermal insulation fiber is prepared by coaxial electrostatic spinning of modified hollow composite microspheres and modified polypropylene into a shell spinning solution; The modified hollow composite microspheres are prepared by reacting tetraethyl orthosilicate with cationic polystyrene microspheres, then reacting with tetrabutyl titanate, and then reacting with a pyrrole mixed solution after calcination; The modified polypropylene is prepared by reacting 10-undecenol protected by triisobutylaluminum with propylene, and then reacting with amino-protected 3-amino-3-(3,5-di-tert-butyl-4-hydroxyphenyl)-propionic acid, immersing in glacial acetic acid and then drying.
2. A method for preparing a hollow thermal insulation fiber, characterized in that: The method comprises the following preparation steps: (1) Cationic polystyrene microspheres, ammonia water and anhydrous ethanol are mixed in a mass ratio of 1: (2-4): (10-20), and tetraethyl orthosilicate, triethanolamine and anhydrous ethanol are mixed in a mass ratio of 1: (0.6-0.8): (13-17) and added dropwise at a rate of 1-3 ml / L. After the addition is completed, the mixture is stirred at 200-400 r / min at 35-45 °C for 4-6 h, cooled to room temperature, and centrifuged to separate the precipitate. The precipitate is washed with deionized water for 3-5 times, and vacuum dried at 55-65 °C for 4-6 h to obtain cationic polystyrene silica microspheres; cationic polystyrene silica microspheres, Deionized water and anhydrous ethanol are mixed in a mass ratio of 1: (3-5): (8-12) and ultrasonicated for 20-40 minutes, tetrabutyl titanate (3-5 times the mass of cationic polystyrene silica microspheres) is added dropwise at a rate of 1-3 ml / L, and the pH is adjusted to 4.8-5.2 with acetic acid. After the addition is completed, the mixture is stirred at 200-400 r / min at 75-85°C for 4-6 hours, and the precipitate is separated by centrifugation. The precipitate is washed with deionized water for 3-5 times, vacuum dried at 55-65°C for 4-6 hours, and calcined at 450-550°C in a muffle furnace for 3-5 hours to obtain hollow composite microspheres of titanium dioxide and silicon dioxide. (2) The hollow composite microspheres and deionized water were mixed at a mass ratio of 1:(14-16), stirred at 300-500 r / min at 0-4°C, and the pyrrole mixture of 3-7 times the mass of the hollow composite microspheres was uniformly added dropwise within 10-15 min. After the addition was completed, stirring was continued for 25-35 min. A 1% ferric chloride aqueous solution of 14-16 times the mass of the hollow composite microspheres was added dropwise at a rate of 1-1.2 mL / min. After the addition was completed, stirring was continued for 10-12 h. The precipitate was separated by centrifugation, and the precipitate was washed with deionized water and anhydrous ethanol for 3-5 times, respectively, and vacuum dried at 40-50°C for 6-8 h to obtain the modified hollow composite microspheres. (3) Triisobutylaluminum-protected 10-undecanol, 2,6-di-tert-butyl-4-methylphenol, methylaluminoxane, dimethylsilylbis(2-methyl-4-phenylindenyl)zirconium dichloride, and toluene are mixed in a mass ratio of 1: (0.03-0.05): (0.2-0.4): (0.1-0.3): (13-17) and added into a reactor. The reaction temperature is 40-50°C, the propylene pressure is 4 bar, and the reaction time is 15 minutes to obtain a primary product. The primary product is immersed in a hydrochloric acid / ethanol solution for 10-20 minutes, filtered, dissolved in toluene at 90-100°C, and purified to obtain hydroxylated polypropylene; (4) Mix hydroxylated polypropylene, amino-protected 3-amino-3-(3,5-di-tert-butyl-4-hydroxyphenyl)-propionic acid, 90% sulfuric acid solution, and toluene in a mass ratio of 1: (0.6-0.8): (0.2-0.4): (8-12), and stir at 95-105°C and 400-600 r / min for 3-5 hours under a nitrogen atmosphere to obtain a polypropylene composite material; immerse the polypropylene composite material in glacial acetic acid, and stir at room temperature at 300-500 r / min for 2-4 hours to obtain a modified polypropylene; (5) Mix modified polypropylene, modified hollow composite microspheres, dichloromethane, and N,N-dimethylacetamide in a mass ratio of 1: (0.2-0.4): (7-9): (0.8-1.2), and stir at 400-600 r / min for 10-14 h at 15-25 °C to obtain a shell spinning solution; mix polyvinyl alcohol, dichloromethane, and dimethyl sulfoxide in a mass ratio of 1: (5-15): (15-25), and stir at 400-600 r / min for 3-5 h at 20-30 °C to obtain a core spinning solution; load the shell spinning solution and the core spinning solution into syringes respectively, and perform coaxial electrospinning in an electrospinning machine to obtain primary fibers; (6) The nascent fibers were immersed in deionized water, ultrasonically treated at 40-50 °C for 2-4 h, allowed to stand at room temperature for 40-44 h, with the water replaced every 2 h, and vacuum dried at 60-70 °C for 3-5 h to obtain hollow thermal insulation fibers.
3. The method for preparing a hollow thermal insulation fiber according to claim 2, characterized in that: The cationic polystyrene microspheres in step (1) are nano-scale cationic polystyrene microspheres.
4. The method for preparing a hollow thermal insulation fiber according to claim 2, characterized in that: The pyrrole mixed solution in step (2) is prepared by mixing pyrrole, pyrrole-3-carboxaldehyde and anhydrous ethanol in a mass ratio of 1: (0.3-0.4): (12-14).
5. The method for preparing a hollow thermal insulation fiber according to claim 2, characterized in that: The triisobutylaluminum-protected 10-undecenol in step (3) is prepared by dropping triisobutylaluminum into 10-undecenol with a molar number of 0.7 to 0.9 times that of triisobutylaluminum at 0° C. under a nitrogen atmosphere, and stirring at 400 to 600 r / min for 3 to 5 hours.
6. The method for preparing a hollow thermal insulation fiber according to claim 2, characterized in that: The reaction process of preparing hydroxylated polypropylene in step (3) is as follows: 。 7. The method for preparing a hollow thermal insulation fiber according to claim 2, characterized in that: The preparation method of the hydrochloric acid / ethanol solution in step (3) is as follows: hydrochloric acid and anhydrous ethanol are mixed in a mass ratio of 1:
5.
8. The method for preparing a hollow thermal insulation fiber according to claim 2, characterized in that: The preparation method of the amino-protected 3-amino-3-(3,5-di-tert-butyl-4-hydroxyphenyl)-propionic acid in step (4) is as follows: 3-amino-3-(3,5-di-tert-butyl-4-hydroxyphenyl)-propionic acid, di-tert-butyl dicarbonate, 1 mol / L sodium hydroxide solution, and tert-butanol are mixed in a mass ratio of 1: (1.3-1.7): (2-4): (8-12), stirred at room temperature at 300-500 r / min for 2-4 hours, and obtained by recrystallization.
9. The method for preparing a hollow thermal insulation fiber according to claim 2, characterized in that: The coaxial electrospinning process parameters of step (5) are: shell layer propulsion rate 0.9 ml / h, core layer propulsion rate 0.3 ml / h, voltage 23 kV, receiving distance 12 cm, and ambient humidity 40-50%.
Citation Information
Patent Citations
Hollow polystyrene plastic spheres, and preparation method and application thereof
CN103387691A
